Antioxidant effect of Cannabis sativa L. resin associated with Larrea divaricata Cav. extract: synergism, additivity and antagonism - Saint Martin, Elina Malén (2022)
Cannabis sativa L. (Cannabaceae) is used as anticonvulsant in refractory epilepsy. Convulsions induce oxidative stress in the brain.Synergistic interactions between plants could improve the therapeutic and reduce adverse effects. Larrea divaricata Cav.’s(Zygophylliaceae) antioxidant activity is well-documented. The aim of this work was to evaluate the antioxidant activity of an ethanolicextract of C. sativa (CSR), study cannabidiol’s (CBD) participation and evaluate the possible synergistic effect of CSR with an aqueousextract of L. divaricata (LE). Antioxidant activity was determined by the 1,1-diphenyl-2-picryhydrazyl (DPPH) and the lipid peroxidationassays. For the DPPH assay, the inhibitory concentration 50 (IC50) were: CSR=19.82 ±1.47 µg/ml, LE=24.18±0.54µg/ml,CBD=12.49 ± 0.79µg/ml. The IC50 values for the combinations: CSR + LE 25 µg/ml=2.91±0.10µg/ml (p<0.001), CBD + LE 25µg/ml=4.19±0.11µg/ml (p<0.01). Combination indexes (CI) were: 15 µg/ml CSR / 25 µg/ml LE=0.38 (significant synergism), 10 µg/mlCBD / 25 µg/ml LE=0.39 (significant synergism). IC50 values for the lipid peroxidation assay: CSR=30.50±3.00µg/ml,LE=630.95±63.00µg/ml, CBD=10.20±1.00µg/ml. The IC50 values of the best combinations: CSR + 500 µg/ml LE=2.39±0.10µg/ml (p<0.0001), CBD + 500 µg/ml LE=2.19±0.18 µg/ml (p<0.0001); CI values: 10 µg/ml CSR /500 µg/ml LE=0.16 (strong synergism), 3 µg/mlCSR /500 µg/ml LE=0.36 (significant synergism). Conclusions: CBD is involved in CSR antioxidant activity. LE acted synergistically withCSR in both assays. CSR-LE association at optimal concentrations could be a good option to reach a significant synergism (CI<1). Atlow doses, the combination of CSR and LE could be used as co-adjuvant for the treatment of epilepsy to manage oxidative stress.